Negative Regulation of GmNAC35 by miR164 Enhances Drought Tolerance in Soybean - Wentao Hu; Man Zhang; Jie Lu; Miaomiao Zhang; Reqing He; Youlin Zhu; Dong Wang; Liyun Jiang (Agronomy, 2025)
Soybean (Glycine max (L.) Merr.) is a critical crop in China, serving as a primary source of food, oil, and animal feed. Drought stress significantly impacts soybean growth and yield. MicroRNAs (miRNAs) play crucial roles in plant drought responses. The miR164 family is highly conserved across plant species and has been shown to participate in drought responses in a range of plants, yet the function of miR164 in soybean remains unclear. In this study, we identified GmNAC35 as a direct target of miR164 through published degradome sequencing data and 5′ RLM-RACE assays. Under drought stress, miR164 members (e.g., MIR164a, MIR164f, and MIR164k) rapidly down-regulated, reaching their lowest expression at 2 h and returning to basal levels within 6 h. Conversely, GmNAC35 showed an inverse pattern, indicating negative regulation by miR164. Overexpression of GmNAC35 enhanced drought tolerance in transgenic soybean plants, as evidenced by higher survival rates and reduced water loss. Transcriptomic analysis revealed that GmNAC35 modulates stress-responsive pathways, including ABA signaling and phenylpropanoid biosynthesis. Our findings indicate that miR164 negatively regulates GmNAC35, a positive regulator of drought tolerance. This enhances our understanding of the molecular mechanisms of drought tolerance in soybean and may inform strategies for breeding drought-resistant varieties.